Transabdominal Approach for Chylorrhea after Esophagectomy by Using Fluorescence Navigation with Indocyanine Green - Takeshi Matsutani; Atsushi Hirakata; Tsutomu Nomura; Nobutoshi Hagiwara; Akihisa Matsuda; Hiroshi Yoshida; Eiji Uchida (Case Reports in Surgery)
A 70-year-old man who underwent two sessions of thoracoscopy-assisted ligation of the thoracic duct to treat refractory chylorrhea after radical esophagectomy for advanced esophageal cancer received conservative therapy. However, there was no improvement in chylorrhea. Then, transabdominal ligation of the lymphatic/thoracic duct at the level of the right crus of the diaphragm was performed using fluorescence navigation with indocyanine green (ICG). The procedure successfully reduced chylorrhea. This procedure provides a valid option for persistent chylothorax/chylous ascites accompanied by chylorrhea with no response to conservative treatment, transthoracic ligation, or both.